(untitled) (Proceedings of Southern Federal University. Philology, 2018)
Marina V. Laskova, Elena A. Fetisenko (Rostov-on-Don, Russian Federation) The article is devoted to the peculiarities of football talk verification in the context of linguistic analysis. Commentary as a special type of speech activity allows to specify unique characteristics of a linguistic persona considered by us as a connecting link wile interpreting game with a target audience and current events. The difference of stylistic markers used in professional sphere permits not only to hold addressee’s attention, but also identify cross-cultural content of the broadcast. Key words: football talk, sport discourse, cognitive metaphor, sport jargon. DOI 10.23683/1995-0640-2018-1-151-154